2019
DOI: 10.1002/cam4.2506
|View full text |Cite
|
Sign up to set email alerts
|

LMP1‐positive extracellular vesicles promote radioresistance in nasopharyngeal carcinoma cells through P38 MAPK signaling

Abstract: Radioresistance has been one of the impediments to effective nasopharyngeal carcinoma (NPC) therapy in clinical settings. Epstein‐Barr virus (EBV) encoded latent membrane protein 1 (LMP1) is expressed in NPC and has potent effects on radioresistance. It has been detected in extracellular vesicles (EVs) or exosomes and shown to promote tumor proliferation and invasive potential. However, whether LMP1‐positive EVs can confer radioresistance to cancer cells and the mechanism used to promote radioresistance need t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 40 publications
1
42
0
Order By: Relevance
“…Further, nasopharyngeal carcinoma cells expressing EBV gene BHRF1 recovered faster after 60 Co radiation with higher cell proliferative rate and colony formation ability, beside a greater tumor formation in nude mice compared to control groups ( 207 ). This is in line with the EBV LMP1-induced proliferation, invasion, apoptosis suppression, and radioresistance in NPC cells ( 208 ).…”
Section: Introductionsupporting
confidence: 76%
“…Further, nasopharyngeal carcinoma cells expressing EBV gene BHRF1 recovered faster after 60 Co radiation with higher cell proliferative rate and colony formation ability, beside a greater tumor formation in nude mice compared to control groups ( 207 ). This is in line with the EBV LMP1-induced proliferation, invasion, apoptosis suppression, and radioresistance in NPC cells ( 208 ).…”
Section: Introductionsupporting
confidence: 76%
“…The expressions of cleaved caspase‐3, caspase‐8, caspase‐9, and PARP were progressively upregulated with the increase in CA dosage in both HONE‐1 (Figure 4A,B) and NPC‐39 cell lines (Figure 4C,D). Moreover, numerous studies have speculated that the molecular mechanism of the MAPK pathways participates in cell apoptosis . Thus, the effect of CA on the phosphorylation of MAPK, the upstream pathway for caspases, was also tested.…”
Section: Resultsmentioning
confidence: 99%
“…[25][26][27] Zhang et al found that exosomes derived from latent membrane protein 1-positive NPC cells could induce recipient NPC cell proliferation and invasion and suppress apoptosis, especially promote radioresistance. 28 Thus, we suppose that circMYC is a potential target to overcome radioresistance in patients with NPC.…”
Section: Discussionmentioning
confidence: 99%